Literature Review: Inovasi Teknologi Ergonomis dalam Peningkatan Efisiensi dan Kesehatan Pekerja di Era Industri 4.0 - Pitto Pratiwi Pratiwi; novrika silalahi; Rizka Annisa; Muhraza Siddiq; Fithri Handayani Lubis (Jurnal Penelitian Kesmasy, 2026)
The Fourth Industrial Revolution has significantly transformed workplace ergonomics through the integration of advanced technologies such as wearable sensors, artificial intelligence (AI), exoskeletons, and markerless motion capture systems. This literature review aims to examine recent innovations in ergonomic technologies that enhance work efficiency while safeguarding workers’ health and safety. Findings from studies published between 2023 and 2025 indicate that these technologies substantially reduce the risk of work-related musculoskeletal disorders, improve productivity, and enable real-time monitoring of workers’ physical conditions. Wearable sensors and AI-based systems play a crucial role in detecting hazardous postures and providing corrective feedback, whereas exoskeletons effectively reduce biomechanical strain during physically demanding tasks. Despite these promising outcomes, several challenges remain. The adoption of ergonomic technologies is often hindered by limited technical validation, inadequate user training, and ethical issues concerning worker data privacy. Moreover, user acceptance is influenced by factors such as comfort, trust, and perceived usefulness of the technology. Emerging debates also highlight potential risks of workplace discrimination associated with data-driven systems. Consequently, a human-centered design approach is essential to ensure that ergonomic innovations prioritize human well-being rather than solely focusing on operational efficiency. This study concludes that the success of ergonomic technologies in the Industry 4.0 era should be evaluated not only by their contribution to productivity but also by their ability to promote long-term occupational health, safety, and overall worker well-being.